2021
DOI: 10.1107/s1600577521007943
|View full text |Cite
|
Sign up to set email alerts
|

Diamond channel-cut crystals for high-heat-load beam-multiplexing narrow-band X-ray monochromators

Abstract: Next-generation high-brilliance X-ray photon sources call for new X-ray optics. Here we demonstrate the possibility of using monolithic diamond channel-cut crystals as high-heat-load beam-multiplexing narrow-band mechanically stable X-ray monochromators with high-power X-ray beams at cutting-edge high-repetition-rate X-ray free-electron laser (XFEL) facilities. The diamond channel-cut crystals fabricated and characterized in these studies are designed as two-bounce Bragg reflection monochromators directing 14.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…All photographs were taken on a background of a 0.5 mm reference grid. Shvyd'ko et al, 2021;Pradhan et al, 2022) from the selected plates and furnished with strain-relief cuts, as shown in Figs. 2(b), 2(c) and 4.…”
Section: High-reflectivity Diamond Crystal Mirrorsmentioning
confidence: 99%
“…All photographs were taken on a background of a 0.5 mm reference grid. Shvyd'ko et al, 2021;Pradhan et al, 2022) from the selected plates and furnished with strain-relief cuts, as shown in Figs. 2(b), 2(c) and 4.…”
Section: High-reflectivity Diamond Crystal Mirrorsmentioning
confidence: 99%
“…However, some defects or dislocations can also be seen on this and other characterized and selected diamond crystals. Using these results, the best region on each diamond (working areas) is identified and the crystal is cut with a laser 24,35,36 beam according to the pattern shown in Fig. 2 in such a way that the crystal defects are outside the working areas.…”
Section: High-reflectivity Diamond Crystal Mirrorsmentioning
confidence: 99%